Klasifikasi Atribut Pelayanan Mobile Banking dengan Kano Model Berdasarkan Dimensi E-Servqual - Safi'i, Imam (Universitas Serang Raya, 2018)
This study aims to determine the classification of mobile banking services that improve customer satisfaction based on the dimensions of E-Servqual using the Kano Model method. The classification is needed so that the banks were able to make improvements and innovations in the performance of the quality of their mobile banking services. From the results of data processing using Kano, it is known that the service attributes that need to be improved are the m-banking facility, which features a cash withdrawal service via ATM. This will have a major impact on customer satisfaction because these attributes have the highest satisfaction coefficient value of 0.67 in one-dimensional classification. Furthermore, service attributes that need to be improved and innovated are m-banking has a fast application reactivation service with a satisfaction coefficient of 0.61 in the attractive classification